Manfaat dan potensi pengembangan tanaman binahong (Anredera Cordifolia) - 'Azza, Arikatul (Maliki Interdisciplinary Journal, 2024)
Binahong plant is one of the medicinal plants originating from West Java, which has various extraordinary health benefits that can provide promising economic potential. Binahong leaves are rich in antioxidants, vitamins and minerals that have properties to increase endurance, improve digestion, and treat various diseases. Binahong itself has a lot of potential in its development such as as a medicinal raw material, food products, cosmetics, and ornamental plants. the development of this medicinal plant needs to be encouraged, in order to improve the welfare of the community.